Sex Workers' Religiousity and Faith in God: Case Study on “Ayam Kampus” in East Java, Indonesia - Rijal, Syamsul; El-Rumi, Umiarso (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2018)
Prostitution is often called to be a social disease that is far from anchoring the values of religiousness, especially diversity. It is normal if the stigma of tilting towards sex workers arises from insults, mocks, until the behavior of ignorance shown by the clergy. Even though sex workers are outside the circle of prostitution, they are